1993
DOI: 10.1098/rspa.1993.0060
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent imaging of thin specimens using coherently scattered electrons

Abstract: We consider the imaging of phase objects using a scanning transmission electron microscope equipped with a large inner-angle annular detector. We show, contrary to popular expectation, that incoherent imaging theory can be used to describe the imaging process in a plane perpendicular to the optical axis. Interference effects between atoms possessing the same projected coordinates must, however, be considered explicitly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…(7) stiil holds. the object function may show a non-linear thickness dependence (see for example Jesson and Pennycook, 1993). However, the phase-object approach taken above demonstrates the principles of how incoherent phase-contrast can be achieved.…”
Section: Incoherent Imaging From Coherent Interferencementioning
confidence: 97%
“…(7) stiil holds. the object function may show a non-linear thickness dependence (see for example Jesson and Pennycook, 1993). However, the phase-object approach taken above demonstrates the principles of how incoherent phase-contrast can be achieved.…”
Section: Incoherent Imaging From Coherent Interferencementioning
confidence: 97%
“…Optical sectioning is now opposed by the tendency of the columns to channel the electrons. Beams incident near the optic axis couple efficiently into the 1 s Bloch state, which before aberration correction was the dominant contribution to the ADF image (Pennycook & Jesson 1990Jesson & Pennycook 1993, 1995Nellist & Pennycook 1999). After aberration correction, the outer beams passing through the outer regions of the objective aperture are now so far from the zone axis that they do not channel strongly and therefore still tend to come to a focus as if propagating in free space.…”
Section: New Possibilities With Aberration-corrected Scanning Transmimentioning
confidence: 99%
“…As explained by Jesson & Pennycook (1993), transverse coherence is broken primarily as a result of detector geometry. By considering two neighbouring atoms in the transverse plane they showed that, when integrating over an annular detector of sufficiently high inner angle v i , destructive interference effectively cancels out coherent scattering contributions.…”
Section: Incoherent Imaging In Stem: An Inverse Problemmentioning
confidence: 99%
“…Although primarily incoherent, Jesson & Pennycook (1995) showed that rather than representing each column as an array of independently vibrating atoms, scattering can be visualized in terms of an assembly of independent 'packets' of atoms. By retrieving the object function directly from acquired data, it may be possible to gain a greater understanding of effects such as partial coherence in the z-direction directly from the image data.…”
Section: Incoherent Imaging In Stem: An Inverse Problemmentioning
confidence: 99%